Pengaruh Content Marketing dan Influencer Marketing Terhadap Keputusan Pembelian dengan Brand Image Sebagai Variabel Mediasi: Studi pada Pembelian Produk Luxcrime di Kota Malang - Alviana Mawarda; Fani Firmansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One current trend that can spark consumer interest is through the use of marketing content distributed via social media platforms. The main goal of this content creation strategy is to move potential consumers into active consumers. Apart from building good relationships with consumers, Influencer marketing also has a significant impact on online sales. Apart from that, the brand image also has a big influence on purchasing decisions, because not only do consumers pay attention to the content and influence of influencers, but also the image of the brand itself. This research is a type of quantitative research that uses a descriptive approach, involving 128 respondents who are consumers of Luxcrime products in Malang City. The sample was selected purposively, and data was collected via a Google form which was then processed using SEM Pls 3.0 software. The research results show that Influencer marketing and brand image have a significant impact on purchasing decisions, while Content Marketing does not have a significant impact. In addition, brand image can mediate the relationship between Content Marketing and Influencer marketing in purchasing decisions..